Nutritional and antioxidative characterization, antimicrobial and sensorial stability of flaxseed powder supplemented mutton patties - Raheel Suleman; Hira Choudhary; Muhammad Waseem; Jaza Maqbl Alshammari; Muhammad Muzamil; Huan Liu; Tariq Ismail; Muhammad Ammar Khan; Muhammad Qamar; Crossby Osei Tutu (Food Chemistry: X)
Oxidative stress and microbial growth deteriorate food quality and cause safety risks. Therefore, the present study was investigated to explore the nutritional, sensorial, anti-oxidative and anti-microbial attributes of flaxseed powder (FP) supplemented at 2–8 % (i.e., T1-T4) level in mutton patties. Among extracts, the aqueous flaxseed extracts exhibited the highest total phenolic contents (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) activities i.e., 275 mg GAE/g, 75 % and 57 mg/g, respectively. The results exhibited significant increase (p < 0.05) in protein, and ash contents from 10.7 to 20.6 and 1.3–2.4 (g/100 g) on addition of FP at 2–8 % in mutton patties, respectively. Likewise, the mutton patties exhibited significant (p < 0.05) decrease in pH and thiobarbituric acid reactive substances (TBARS) of T1-T4 from 7.1 to 3.4 and 317–46 than control i.e., 6.64–4.12 and 453.75–563 at 0–16 days. Among color of mutton patties, L⁎ values decreased from 37 to 25, while, b⁎ values increased from 10 to 13 on addition of 2–8 % FP in mutton patties at 0–16 days for T1-T4, respectively. A significant decrease (p < 0.05) in total plate counts (TPC), Salmonella and E. coli of mutton patties was recorded in T0-T4 from 4.2 to 2.8, 0.8–0.3, and 2.1–0.3, respectively at 16th day of storage, respectively. Sensory experts rated the T1 (i.e., 2 % FP supplemented mutton patties) owing to their best sensory scores and overall acceptability. Conclusively, owing to better potential of FP in improving the nutritional and microbial quality of mutton patties, the study further suggests its ability to act as a novel functional ingredient of choice in shelf-life extension of other food products.